Transition metal free catalytic hydroboration of aldehydes and aldimines by amidinato silane - Bisai, Milan; Pahar, Sanjukta; Das, Tamal; Sen, Sakya S. (Dalton Transactions, 2017)
The transition metal free catalytic hydroboration of aldehydes and ketones is very limited and has not been reported with a well-defined silicon(iv) compound. Therefore, we chose to evaluate the previously reported silicon(iv) hydride [PhC(NtBu)2SiHCl2], (1) as a single component catalyst and found that it catalyzes the reductive hydroboration of a range of aldehydes with pinacolborane (HBpin) under ambient conditions. In addition, compound 1 can catalyze imine hydroboration. DFT calculation was carried out to understand the mechanism.

Twelve-armed hexaphenylbenzene-based giant supramolecular framework for entrapping guest molecules - Madhu, Suresh; Gonnade, Rajesh G.; Das, Tamal; Vanka, Kumar; Sanjayan, Gangadhar J. (ChemPlusChem, 2018)
Host-guest chemistry is a functional model in supramolecular chemistry for understanding specific process occurring in biological systems. Herein, we describe a rationally designed giant multiarmed hexaphenylbenzene (HPB)-based supramolecular frameworks which encapsulate a variety of guest molecules in the voids of their crystal lattice through the cooperative interplay of multivalency, noncovalent forces and backbone rigidity. In this connection, pseudo-axially substituted twelve-armed hexaphenylbenzene was synthesized and its molecular entrapping nature was studied by varying number of H-bond donor-acceptor sites in the arms. The per-methyl esterified HPB acted as a cavitand to include nonpolar and polar aprotic guests in its crystal structure via C-H center dot center dot center dot pi, C-H center dot center dot center dot O and C-H center dot center dot center dot N interactions. The corresponding amidated HPB showed unprecedented inclusion of ammonia and segregation of the guest molecules according to their polarity in the lattice. Furthermore, this molecular entrapping system has been used to obtain the crystal structure of a hitherto unproven 2-azaallenium intermediate, which had been proposed to be involved in aminomethylation of activated arenes.

Transmetallation vs adduct: diverse reactivity of N,O-ketiminato germylene with [Cp*MCl2](2) (M = Rh or Ir; Cp* = eta(5)-C5Me5) and MCl5 (M = Nb and Ta) - Raghavendra, Beesam; Bakthavachalam, K.; Das, Tamal; Roisnel, Thierry; Sen, Sakya S.; Vanka, Kumar; Ghosh, Sundargopal (Journal of Organometallic Chemistry, 2020)
The reactions of the germylenes, [(Dipp)NCMeCHCORGeCl] (1a: R = Me, 1b: R = Ph) with [Ir2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] led to the formation of the adducts [(Dipp)NCMeCHCORGeClIrCl2Cp*] (3a: R = Me and 3b: R = Ph). On the other hand, [Rh2Cl2(mu-Cl)(2)(eta(5)-Cp*)(2)] does not react with the germylenes (1a and 1b). When the reactions of 1a and 1b are carried out with [Cp*TaCl4], the reaction led to decomposition. The reaction of 1a or 1b with TaCl5 yielded the transmetallated products [(Dipp)NCMeCHCORTaCl4] (4a: R = Me, 4b: R = Ph) with the extrusion of GeCl2. Our theoretical studies show that for, the insertion of TaCl5 to 1a and the formation of 4a with concomitant elimination of GeCl2 is energetically favourable. Extrusion of SnCl2 is also observed when the corresponding stannylene, [(Dipp)NCMeCHCOMeSnCl] was reacted with TaCl5. All these compounds have been characterized by H-1 and C-13 NMR spectroscopy, elemental analysis and the constitution of compounds 1b, 3b, and 4a were confirmed by single-crystal X-ray crystallography. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Adduct formation; Germylenes; Iridium; Ketoiminate; Tantalum; Transmetallation